Hey, I have some troubles with solving the problem below:
Let f: X -> Y and g: Y -> Z be bijective functions.
Prove that (g o f )^(-1) = f^(-1) o g^(-1).
I think I can understand it intuitively, but I don't know how to elaborate it.
Thank you.
Hey, I have some troubles with solving the problem below:
Let f: X -> Y and g: Y -> Z be bijective functions.
Prove that (g o f )^(-1) = f^(-1) o g^(-1).
I think I can understand it intuitively, but I don't know how to elaborate it.
Thank you.
I think I found the answer in other posts.
http://www.mathhelpforum.com/math-he...ons-proof.html